MILK QUALITY OF ETAWA BREEDING GOATS SEEN FROM CALIFORNIA MASTITIS TEST, ALCOHOL TEST, REDUCTASE TEST, AND BOILING TEST IN RAKA ETAWA FARMING - Ndoy, Maria Ursulin Tasya; Suardana, I Wayan; Mufa, Romy Muhammad Dary (Buletin Veteriner Udayana, 2024)
Milk is a food product of animal origin that has high benefits. The main requirement for milk consumption by the public is good milk quality. This study aims to determine the quality of Etawa breeding goat milk as seen from the California mastitis test, alcohol test, reductase test, and boiling test at Raka Etawa Farm and see the relationship between the California mastitis test (CMT) with the alcohol test, reductase, and boiling test. This study was conducted in a descriptive observational. Sampling using purposive sampling method with sample criteria taken is milk from goat mothers who are in the lactation period. In this study it was found that of the 30 milk samples taken, based on the results of the California mastitis test, there were 15 samples of milk of Etawa breeding goats (50%) experiencing the incidence of subclinical mastitis level III, 11 milk samples (36,7%) experiencing the incidence of subclinical mastitis level II, and as many as 4 milk samples (13,3%) did not experience the incidence of subclinical mastitis. Based on the alcohol test, 26 milk samples (80%) showed positive results and as many as 4 milk samples (20%) showed negative results. The reductase test results showed that 24 samples (80%) had a reductase time of 2 hours and 6 samples (20%) showed a reductase time of 1 hour. The boiling test results showed that 26 milk samples (86,7%) were positive and 4 milk samples (13,3%) had negative results. There was no significant relationship between the CMT test and alcohol test and the CMT test and reductase test (P > 0.05). There was a significant relationship between the CMT test and boiling test (P < 0.05) on the quality of milk of Etawa breeding goats at Raka Etawa Farm. It can be concluded that the majority of Etawa breeding goat milk at Raka Etawa Farm is of poor quality. Cage hygiene, cleaning the udder before milking, and always using gloves during milking need to be considered to produce good quality milk by applicable standards.